2019
DOI: 10.1101/536474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperament profile and its association with the vulnerability to smartphone addiction of medical students in Indonesia

Abstract: Temperament profiles of an individual with high novelty seeking and low harm avoidance have been reported to be related to substance addiction, but smartphone addiction could be different from substance addiction. Medical students have high exposure to smartphone use. Screening their risk of smartphone addiction based on the temperament profile may help in deciding best prevention approach. This research aimed to examine the temperament profile and its association with vulnerability to smartphone addiction of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(44 reference statements)
2
11
0
1
Order By: Relevance
“…Our results showed that higher depressive temperament was significantly associated with more phubbing, in accordance with a previous study [32]. Similar results were found in many previous studies where smartphone addiction and Internet addiction were found associated with higher depression [19,20,52].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that higher depressive temperament was significantly associated with more phubbing, in accordance with a previous study [32]. Similar results were found in many previous studies where smartphone addiction and Internet addiction were found associated with higher depression [19,20,52].…”
Section: Discussionsupporting
confidence: 93%
“…The cyclothymic temperament is characterized by chronic cycling between mood polarities and unstable self-esteem and energy; the hyperthymic temperament by increased energy and optimism [31], the irritable temperament by irritable and angry behavior; the anxious temperament by a tendency to worry; and depressive temperament by low levels of energy, introversion and worrying [30]. Previous findings showed a strong association between phubbing and these five temperaments [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harm-avoidant temperament and impulsivity are well-known risk factors of PSU and other addictive disorders [ 12 , 42 , 57 , 58 ]. These risk factors may act as biological vulnerabilities to PSU.…”
Section: Discussionmentioning
confidence: 99%
“…Esse valor, ainda que considerado alto por alguns autores, é inferior à média observada em estudos que abordam jovens com vícios e dependências no uso do celular 16,17 .…”
Section: Procedimentos Metodológicosunclassified